2014
DOI: 10.1063/1.4864151
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fluid flow on the solidification of Ni2B from the undercooled melt

Abstract: In this work, we study the effect of fluid flow on the growth dynamics during solidification of tetragonal Ni 2 B from the undercooled melt. Different experimental techniques are applied to generate varying fluid flow velocities in undercooled samples, electromagnetic levitation under 1 g conditions (1 g EML) and in reduced gravity (lg EML) as well as the melt-fluxing technique and electrostatic levitation. The propagation of the solid-liquid interface apparent on the surface of solidifying samples is observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 65 publications
2
22
0
Order By: Relevance
“…13 and details of calculations in paper [92]). The applicability of the theory is confirmed by its agreement with experiment under terrestrial and reduced gravity conditions in EML and ESL facilities and with the use of the melt fluxing technique [93]. Further development of research and independent verification of the adequacy of the above models for the available experimental data on the changes of growing crystal morphology should be focused on numerical simulations of solidification, taking account of the anisotropic properties of moving liquid±crystal interfaces and convective flows.…”
Section: Comparison Of Theoretical Predictions With Experimental Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…13 and details of calculations in paper [92]). The applicability of the theory is confirmed by its agreement with experiment under terrestrial and reduced gravity conditions in EML and ESL facilities and with the use of the melt fluxing technique [93]. Further development of research and independent verification of the adequacy of the above models for the available experimental data on the changes of growing crystal morphology should be focused on numerical simulations of solidification, taking account of the anisotropic properties of moving liquid±crystal interfaces and convective flows.…”
Section: Comparison Of Theoretical Predictions With Experimental Resultsmentioning
confidence: 67%
“…[92]), were utilized to calculate the dendritic growth rate as a function of supercooling. In addition to this set of equations, the peculiarities of the kinetic phase diagram were taken into account, determined by the liquidus slope and segregation coefficient in the functions of Ni 2 B crystal growth rate [92,93]. The results of calculations are shown in Fig.…”
Section: Comparison Of Theoretical Predictions With Experimental Resultsmentioning
confidence: 99%
“…A preliminary test of the AG theory has already been conducted using a two-dimensional formalism [20]. It was shown that the AG theory can provide a satisfactory explanation of the dendritic growth velocities observed in containerlessly undercooled intermetallic compounds in the presence of a convective flow in a bulk volume [20,21]. However, phase field modeling suggested that the influence of melt convection on a three-dimensional tip is more pronounced than on a two-dimensional tip [17,22].…”
mentioning
confidence: 99%
“…These are EML on Earth (forced convection), EML in reduced gravity (reduced forced convection), melt fluxing technique (natural convection), melt fluxing in a strong external magnetic field (reduced natural convection), and electrostatic levitation on small samples (almost no convection). [87] 7. Intermetallic compound Ni 2 B: different levels of convection…”
Section: Intermetallic Compound Al 50 Ni 50 : Disorder Trappingmentioning
confidence: 99%